Analysis Of The Transformation Of Mustahik Into Muzakki Through The Economic Empowerment Program Of The Prosperous Village Livestock In The Amil Zakat Institution Nurul Hayat Jember - Dafid Rosyidi; Abdul Rokhim; Nurul Widyananti Islami Rahayu (Cita konsultindo, 2024)
Zakat is an important instrument in creating the Indonesian economy which is used as an effort to prosper the people. The potential of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) in Indonesia is very high, considering the majority of the population in Indonesia is Muslim. The potential for zakat in Indonesia is very large, reaching Rp327 trillion per year. One of them is the Nurul Hayat Jember foundation with very many programs that are able to contribute in the fields of education, economic empowerment, health, da’wah and community services. This research focuses on the transformation of mustahik into muzakki through the economic empowerment program of the prosperous village livestock and the economic condition of mustahik before and after undergoing the economic empowerment program of the prosperous village livestock at Nurul Hayat Jember. Through a qualitative approach, researchers describe the transformation process in the economic empowerment program, and describe the implementation of the economic empowerment program, systematically. The results of this study explain that (1) the transformation process takes place through stages involving changes in perceptions, attitudes, and mindsets. The concept of economic empowerment and the social and economic transformations that occur are a reflection of historical changes in mustahik conditions. (2) The Livestock Economic Empowerment Program succeeded in creating a significant positive impact in improving the economic conditions, welfare, and independence of the mustahik. These positive impacts include improved economic welfare, social inclusion, and community development, as well as contributions to local economic growth.